An increasing role for solvent emissions and implications for future measurements of volatile organic compounds. (30th October 2020) - Lewis, Alastair C.; Hopkins, Jim R.; Carslaw, David C.; Hamilton, Jacqueline F.; Nelson, Beth S.; Stewart, Gareth; Dernie, James; Passant, Neil; Murrells, Tim
Abstract : Volatile organic compounds (VOCs) are a broad class of air pollutants which act as precursors to tropospheric ozone and secondary organic aerosols. Total UK emissions of anthropogenic VOCs peaked in 1990 at 2, 840 kt yr −1 and then declined to approximately 810 kt yr −1 in 2017 with large reductions in road transport and fugitive fuel emissions. The atmospheric concentrations of many non-methane hydrocarbons (NMHC) in the UK have been observed to fall over this period in broadly similar proportions. The relative contribution to emissions from solvents and industrial processes is estimated to have increased from approximately 35% in 1990 to approximately 63% in 2017. In 1992, UK national monitoring quantified 19 of the 20 most abundant individual anthropogenic VOCs emitted (all were NMHCs), but by 2017 monitoring captured only 13 of the top 20 emitted VOCs. Ethanol is now estimated to be the most important VOC emitted by mass (in 2017 approx. 136 kt yr −1 and approx. 16.8% of total emissions) followed by n -butane (52.4 kt yr −1 ) and methanol (33.2 kt yr −1 ). Alcohols have grown in significance representing approximately 10% of emissions in 1990 rising to approximately 30% in 2017. The increased role of solvent emissions should now be reflected in European monitoring strategies to verify total VOC emission reduction obligations in the National Emissions Ceiling Directive. Adding ethanol, methanol, formaldehyde, acetone, 2-butanone and 2-propanol to the existing NMHC measurements would provide full coverage of the 20 most significant VOCs emitted on an annual mass basis. This article is part of a discussion meeting issue 'Air quality, past present and future'.